2003
DOI: 10.1111/j.1365-2621.2003.tb08273.x
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation Kinetics of Food Poisoning Microorganisms by Carbon Dioxide and High Hydrostatic Pressure

Abstract: The inactivation kinetics of food poisoning microorganisms using a combined treatment of carbon dioxide (CO 2 ) with high hydrostatic pressure (HHP) was investigated. Staphylococcus aureus, Fusarium oxysporum, and Fusarium sporotrichioides were totally inactivated by a combined treatment of carbonation and HHP at 500 MPa. Bacillus subtilis, a spore forming bacteria, were not completely inactivated after the combined treatment. The microorganisms treated by carbonation and HHP were exponentially reduced in a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 17 publications
2
24
0
2
Order By: Relevance
“…This trend has been observed in previous studies (Ballestra and others 1996; Park and others 2003; Lim and others 2006) which reported that microbial inactivation by DPCD is governed essentially by the transfer rate and the penetration of CO 2 into the cells, the effectiveness of which can be improved by increasing pressure, decreasing the pH of the suspensions and increasing the process temperature. Studies investigating CO 2 under pressure have reported that microbial inactivation is highly dependent on other processing parameters such as residence time and number of pulse cycles as well as the composition of the food (Park and others 2003). Microbial inactivation is also highly dependent on the type of microorganisms present in the food matrix due to distinct microbial cell microstructure and the diffusion of CO 2 into the microbial cells (Ballestra and others 1996).…”
Section: Resultssupporting
confidence: 81%
“…This trend has been observed in previous studies (Ballestra and others 1996; Park and others 2003; Lim and others 2006) which reported that microbial inactivation by DPCD is governed essentially by the transfer rate and the penetration of CO 2 into the cells, the effectiveness of which can be improved by increasing pressure, decreasing the pH of the suspensions and increasing the process temperature. Studies investigating CO 2 under pressure have reported that microbial inactivation is highly dependent on other processing parameters such as residence time and number of pulse cycles as well as the composition of the food (Park and others 2003). Microbial inactivation is also highly dependent on the type of microorganisms present in the food matrix due to distinct microbial cell microstructure and the diffusion of CO 2 into the microbial cells (Ballestra and others 1996).…”
Section: Resultssupporting
confidence: 81%
“…There is interest in using a combination of treatments such as antimicrobial substances included in the product and pressurizing gases such as carbon dioxide (Hong & Pyun, 1999;Park, Park, & Park, 2003;Watanabe et al, 2003). The optimization of stages prior to processing, the use of processing cycles, pressure pulsing, or combined heatepressure processes to obtain shelf-stable products by enhancing the inactivation rate (especially for spores) are also important research issues.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Compared with other organic acids used as acidulants, the specific inhibitive effect of C 0 2 on microorganisms has been demonstrated by some authors (1,8,12,30). The anti microbial effect of C 0 2 during high-pressure carbonation has been attributed to a decrease of intracellular pH, damage to the cell membrane induced by ready penetration of C 0 2 into the cells and dissociation of the C 0 2 within the cells (1,6,31), and cell rupture due to the expansion of C 0 2 within the cells when the pressure is released (24,34). Our previous work has demonstrated that the combination of soluble C 0 2 with pressure of 250 MPa at 30°C in Luria-Bertani broth increased the membrane permeabilization of E. coli cells, as indicated by the uptake of propidium iodide, from 10% up to more than 80%, with complete inactivation (34).…”
Section: Plantarum (A and A) During Storage At 8 °C Following Hhp Trementioning
confidence: 95%
“…The pH of juice also affects the survival of bacteria in pressure-treated juice during subsequent storage (2,4,7). The combined use of dissolved C 0 2 with HHP has been demonstrated to inactivate bacteria such as E. coli and Staphylococcus aureus effectively at mild pressure (23,24,34). However, the combined effect of C 0 2 and HHP may be affected by the matrix and pH of fruit juice.…”
mentioning
confidence: 97%
See 1 more Smart Citation